ShAHRISABZ VA MAYDANAK BALAND TOG‘ TURISTIK MARKAZINING EKOTURISTIK IMKONIYATLARIDAN SAMARALI FOYDALANISh MASALALARI - Yarashev, Q.S.; Badalov, O.B.; Yusupov, B.B. (SCIENCE and SOCIETY, 2025)
The article is devoted to the ecotourism potential of the Shakhrisabz and Maidanak high-mountain tourist centers and their effective use. The main attention is paid to the development of promising tourism sectors in the mountainous and foothill regions of the basin.